Introduction: Special issue on the ethics of anthropology in emergencies - Stellmach, D; Beshar, I (Anthropological Society of Oxford, 2016)
West Africa’s Ebola virus epidemic (December 2013 to January 2016) thrust anthropology into the public eye. It is hard to think of a recent moment when anthropology as a profession has had a higher profile. Anthropologists have been active in the Ebola response, both as policy commentators (Sridhar and Clinton 2014; Abramowitz 2014) and frontline responders (Bedford 2015). On the ground, anthropologists worked alongside other public health professionals to trace patient contacts, manage burial practices and guide both the medical responders on the social dimensions of the outbreak and the general population on the behaviours of the virus and its clinicians (Bedford ibid.).